2023
DOI: 10.3390/healthcare11081143
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age, Gender, Temporality, and Geographical Region on the Prevalence of Obesity and Overweight in Saudi Arabia: Scope of Evidence

Abstract: Objectives: The objectives of this scoping review are to estimate the prevalence of obesity and overweight in the Saudi community and in different age groups, genders, and geographical location, in addition to the change in prevalence over time. Methods: This scoping review of evidence was conducted in accordance with the Joanna Briggs Institute methodology for scoping reviews and was reported following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…It is well recognized that obesity worsens other CVD risk factors by its augmenting effects on dyslipidaemia, high blood pressure, peripheral insulin resistance, and inflammation [ 59 , 60 ]. Based on the results of this study and previous reports from Saudi Arabia [ 61 , 62 ], which showed a distinctive pattern of obesity in Saudi women, obesity management and prevention in women should be focused on weight management around pregnancy and menopause.…”
Section: Discussionsupporting
confidence: 55%
“…It is well recognized that obesity worsens other CVD risk factors by its augmenting effects on dyslipidaemia, high blood pressure, peripheral insulin resistance, and inflammation [ 59 , 60 ]. Based on the results of this study and previous reports from Saudi Arabia [ 61 , 62 ], which showed a distinctive pattern of obesity in Saudi women, obesity management and prevention in women should be focused on weight management around pregnancy and menopause.…”
Section: Discussionsupporting
confidence: 55%
“…This seemingly counteractive result might be attributed to the intricate balance between BMI, hormonal shifts, and reproductive dynamics in individuals with obesity. Enhanced estrogen synthesis by fat tissues might facilitate better implantation probabilities and subsequent pregnancy outcomes [6,7]. Yet, the exact mechanisms necessitate deeper probing in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of these procedures hinges on several determinants, including the patient's weight, gamete quality, and endometrial receptivity [6]. A stark representation of obesity can be observed in the World Health Organization's (WHO) definitions, categorizing individuals with a body mass index (BMI) of 25 or above as overweight and those with a BMI exceeding 30 as obese [7]. Alarmingly, recent research by Wahabi et al disclosed that a staggering almost two-thirds of Saudi women, encompassing all age groups and regions, grapple with obesity [8].…”
Section: Introductionmentioning
confidence: 99%
“…High BMI prevalence has increased among Saudis, particularly among middle-aged individuals [16]. Most of the respondents claimed to have little information about anti-obesity medications.…”
Section: Discussionmentioning
confidence: 99%